Participatory video: Climate change in Nicaragua - The making-of - International Center for Tropical Agriculture (2014)
A video made by CIAT’s researchers to give a ‘look behind the scenes’. This video explains the Participatory Video project and methodology undertaken in Nicaragua in May 2014.